SOCIO-CULTURAL LANDSCAPE OF THE BUKHARA KHANATE IN TRAVEL BOOKS (Multidisciplinary Journal of Science and Technology, 2026)
This article analyzes the socio-cultural landscape of the Bukhara Khanate based on travelogues. In particular, it highlights how the daily life of the city of Bukhara, relations between social classes, customs, religious ceremonies, and cultural environment are described in travelogues written by local and foreign tourists, ambassadors, and scholars. Travelogues are important as a historical source, reflecting not only political events, but also the life of the people, the education system, crafts, trade, and the architectural environment. The article also focuses on the issues of social inequality, spiritual values, and cultural diversity in the Bukhara Khanate from the authors' perspective. The results of the study substantiate the fact that travelogues are an important source in studying the history of the Bukhara Khanate.